2021
DOI: 10.1155/2021/6615400
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Mitochondrial Dynamics: An Emerging Pathogenic Driver of Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is defined as a progressive segmental dilation of the abdominal aorta and is associated with high mortality. The characterized features of AAA indicate several underlying mechanisms of AAA formation and progression, including reactive oxygen species production, inflammation, and atherosclerosis. Mitochondrial functions are critical for determining cell fate, and mitochondrial dynamics, especially selective mitochondrial autophagy, which is termed as mitophagy, has emerged as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
(138 reference statements)
1
6
0
Order By: Relevance
“…While the detection of the ATP synthesis regulatory pathway is novel, it is in line with previous work associating mitochondrial disfunction and AAA [23,24]. On the other hand, previous differential expression studies in microarrays between AAA and control aortic tissue have consistently found associations of immune system pathways with AAA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…While the detection of the ATP synthesis regulatory pathway is novel, it is in line with previous work associating mitochondrial disfunction and AAA [23,24]. On the other hand, previous differential expression studies in microarrays between AAA and control aortic tissue have consistently found associations of immune system pathways with AAA.…”
Section: Discussionsupporting
confidence: 81%
“…Our results indicate that 88 % (22 / 25) of the DEGs coding for the subunits of the complexes that form the electron transport chain are expressed to a lower extent in AAA, suggesting a lower synthesis of ATP in AAA tissue. Mitochondrial dysfunction has previously been studied in the development of AAA [23,24] and other cardiovascular diseases [25] due to its key role in some of the cellular alterations characteristic of cardiovascular diseases, including excessive production of reactive oxygen species, energy depletion, endoplasmic reticulum stress, and activation of apoptosis. However, this is the first time that these metabolic pathways have been characterized in a DEGs study of AAA, confirming the role of mitochondrial dysfunction on AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mtDNA can be released from defective mitochondria and accumulate outside of mitochondria if not properly removed. Thus, the high mtDNA copy number in combination with an increased fission to fusion rate may indicate defects in mitophagy in AAA-SMC, as it has been suggested by others [42]. Clear evidence of defective mitophagy in VSMC and its underlying causes in the course of AAA disease is still pending.…”
Section: Discussionmentioning
confidence: 74%
“…STS-induced cell cycle arrest probably tips the balance between pro and antiapoptotic signals toward apoptosis even though STS may induce cytoprotective mechanism. Indeed, we observed that STS promotes mitochondrial biogenesis, which is associated with improved function, stress resistance and cell survival 35,54,55 . STS stimulates the expression of the master regulator of mitochondrial biogenesis PGC-1α and downstream transcription factor NRF1.…”
Section: Discussionmentioning
confidence: 90%